Motion block based video super resolution - Izadpanahi, Sara; Demirel, Hasan (Academic Press Inc Elsevier Science, 2013)
This paper presents a new video super resolution technique, based on the motion and static areas of the low resolution video frames. In order to separate the motion and static blocks, a block motion estimation method is performed between a reference and its neighboring frames. Among the motion blocks, the occluded blocks are identified using an adaptive threshold applied on each block individually. Structure-adaptive normalized convolution (SANC) reconstruction method is used to generate the high resolution static and motion blocks where discrete wavelet transform (DWT) based interpolation is used to produce the high resolution occluded blocks. The static and motion blocks are combined into a high resolution frame. Finally, a sharpening process is performed on the high resolution frame in order to generate the super resolved high resolution output frame. The experimental results show that the proposed technique provides significantly better qualitative visual results as well as quantitative higher PSNR than the state of the art video super resolution algorithms. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Wavelet transform; Interpolation; De-blurring; Super resolution